Strategi Komunikasi Politik Pasangan Calon Al Haris dan Abdullah Sani Dalam Memenangkan Pilkada Gubernur Jambi Tahun 2020 - Hutapea, Edison Bonartua; Saputra, Dedi (FISIP Universitas Bung Karno, 2024)
This research aims to analyze political communication strategies and inhibiting factors as well as political communication opportunities for the winning team of Al Haris and Abdullah Sani in the Jambi Governor's Pilkada in 2020. In an effort to achieve victory in the 2020 Governor's Pilkada contest in Jambi Province, planning must be carried out. A mature political communication strategy and massive dissemination of issues to the public are important to achieve victory. In this research, researchers used descriptive qualitative methods. Researchers use Political Marketing theory with three approaches, namely; push marketing, pull marketing, pass marketing. There were several steps taken by the winning team of Al Haris and Abdullah Sani during the campaign period, namely in three ways: face-to-face campaign, campaign using social media, and limited open campaign. The obstacles experienced by the winning team of Al Haris and Abdullah Sani in the field were semantic factors, namely, lack of solid coordination and communication between the winning team and distortion of perception, namely, mistakes caused by the narrow thinking of novice voters, making it quite difficult to convey programs. as well as the vision and mission of the candidate pairs. Keywords: Strategy, Communication, Political Communication Strategy, Candidate Pairs